The effect of silane on the biomechanical properties of PEEK/HA composite - Rashidi, Ahmad Ramli (2015)
Bioactive composites containing Polyetheretherketone / Hydroxyapatite (PEEK/HA) were prepared using nanomixer single screw extruder and injection molding. The loading of HA in PEEK matrix was made at different concentrations ranging from 10 wt% to 30 wt%. HA was treated with (3-Aminopropyl) trimethoxysilane, coupling agent, and compared to untreated HA in PEEK/HA composite to evaluate the changes in the biomechanical properties and cytotoxicity. The biomechanical properties including elongation at break and impact properties were assessed. Cell proliferation test was also performed with U937 cell line in the silane treated and untreated PEEK/HA composite. The results showed that silane coupled PEEK-HA had in general improved biomechanical properties than untreated HA and did not show cytotoxicity in vitro.